Revealing the power play: Unraveling the dynamic environment's influence on intangible resources and sustainable competitive advantage - Rahmat, Muhammad Wadud (Jurnal Siasat Bisnis, 2024)
Purpose – The objective of this study is to examine the impact of the dynamic environment on the relationship between intangible resources and sustainable competitive advantage in large and medium-sized manufacturing firms operating across various sectors.Design/methodology/approach – The research sample was selected using cluster random sampling, which is based on company size, namely large and medium-sized companies only, totalling 257 companies as the unit of analysis. A questionnaire was utilized to collect data. While the study employed residual technique and the Hayes (2012) method for variable assessment, the primary method used was a causal analysis.Findings – The findings indicate that the dynamic environment does not act as a moderating variable, implying that the sustainability of the organization is unaffected by the firm’s dynamic environment.Research limitations/implications – Research findings can play a pivotal role in corporate strategy, enabling companies to reach a sustainable competitive advantage by closely monitoring environmental changes. Practical implications – This research can assist companies in developing business strategies that are more adaptive to environmental changes, enabling them to actively monitor and identify emerging opportunities and threats. By doing so, companies can take appropriate steps to maintain their competitive advantage.Originality/value – Previous researchers have rarely conducted this research, primarily due to a lack of understanding on how to effectively connect dynamic environments with intangible resources in order to achieve sustainable competitive advantage.